(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تُعدّ الصخور الكلسية الحوارية من الصخور الرسوبية. يمثل الحوار الصخر النقي والطري، ويتكون من البقايا العضوية مثل الكوكوليت والمنخربات بشكل رئيس، تصل فيه نسبة كربونات الكالسيوم إلى أكثر من 90% ويوجد عادة على شكل طبقات ثخينة. تعدّ الكربونات من الفلزات الفعالة كيميائيا" وتتميز بخاصتين هما الطراوة والقابلية للانحلال بالماء، الأمر الذي يؤثر سلبا" في خواص الصخور الجيوهندسية عند استخدامها كمواد بناء في الردميات أو عند التأسيس عليها. يعرض البحث نتائج الاختبارات المنفذة من قبل الباحث على عينات تم جمعها من شمال سورية. شملت التجارب تحديد الوزن النوعي، والكثافة، والمسامية، ومقاومة الصخور للقص والكسر. The chalky lime stones are sedimentary rocks. Chalk is a pure, soft, well-jointed limestone composed primarily of the calcareous remains of microorganisms called coccoliths and foraminifera. Pure white chalk contains more than 90% CaCO3 and is usually found in thick beds. Carbonates are chemically reactive; they are soft and soluble in water that influences their engineering performance both as rock materials and as bedrock under the foundations. However, this paper describes the results of laboratory experiments on the different specimens of the chalky lime stones collected from the north of Syria.Their specific gravities, dry and saturated densities and porosity were determined. The porosity increased and the dry densities decreased. Furthermore, the internal angel of friction decreased with increasing porosity. The unconfined compressive strength, shear strength and related properties were also determined.